2008
DOI: 10.1111/j.1473-2165.2008.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention to variation in female facial skin color distribution

Abstract: Variation in visible skin color distribution (independent of facial form and skin surface topography) is able to selectively attract people's attention toward female faces, and this higher attention results in more positive statements about a woman's face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 37 publications
1
57
0
Order By: Relevance
“…Eye movements are important visual attention measurements because where a person looks or fixates on indicates the initial stage before the stimulus is processed and encoded (Yantis, 2005). Moreover, attractiveness is a strong factor in determining visual attention, as demonstrated in previous research showing that (1) people focus more attention on relevant versus irrelevant information (Suschinsky et al, 2007), (2) infants gaze longer at attractive or familiar adults (Langlois et al, 1987), and (3) men stare longer at attractive female faces (Fink et al, 2008;Maner, DeWall, & Gailliot, 2008). Specifically, eye tracking studies show that people look longer at images that portray the opposite sex and limit their viewing of the face when the image contains erotic content (Lykins, Meana, & Kambe, 2006; see also Rupp & Wallen, 2007).…”
Section: Eye Movements and Attractivenessmentioning
confidence: 96%
“…Eye movements are important visual attention measurements because where a person looks or fixates on indicates the initial stage before the stimulus is processed and encoded (Yantis, 2005). Moreover, attractiveness is a strong factor in determining visual attention, as demonstrated in previous research showing that (1) people focus more attention on relevant versus irrelevant information (Suschinsky et al, 2007), (2) infants gaze longer at attractive or familiar adults (Langlois et al, 1987), and (3) men stare longer at attractive female faces (Fink et al, 2008;Maner, DeWall, & Gailliot, 2008). Specifically, eye tracking studies show that people look longer at images that portray the opposite sex and limit their viewing of the face when the image contains erotic content (Lykins, Meana, & Kambe, 2006; see also Rupp & Wallen, 2007).…”
Section: Eye Movements and Attractivenessmentioning
confidence: 96%
“…Attractiveness, particularly in women, comprises a set of physical traits that captures the attention of the opposite sex (Maner, Gailliot, & DeWall, 2007). Eye-tracking research has shown that participants of both sexes look preferentially at faces of attractive women (Fink et al, 2008;Maner, DeWall, & Gailliot, 2008). However, there is currently only limited information on how men process female WHR when making attractiveness judgments.…”
Section: Introductionmentioning
confidence: 97%
“…There is growing evidence that facial attractiveness actively captures attention (Maner, DeWall, & Gailliot, 2008;Maner, Gailliot, & DeWall, 2007) and that participants purposefully use facial features when judging the attractiveness of female faces (Shimojo, Simion, Shimojo, & Scheier, 2003). Female faces with an even complexion are judged to be highly attractive and also receive the most visual attention during eye-tracking studies (Fink et al, 2008).…”
Section: Introductionmentioning
confidence: 99%